Influence of obesity on osseointegration of implants with different surface treatments: A preclinical study - Silva, Bruno Luís Graciliano [UNESP]; Sánchez-Puetate, Julio Cesar [UNESP]; Pinotti, Felipe Eduardo [UNESP]; Marcantonio, Camila Chierici [UNESP]; Pedroso, Gabriel Gimenez [UNESP]; Junior, Elcio Marcantonio [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (My University, 2023)
Objective: The aim of the present study was to evaluate the effect of obesity on the osseointegration of implants with hydrophobic and hydrophilic surfaces. Materials and Methods: Sixty-four male rats were distributed among four experimental groups: H-HB (Healthy/Hydrophobic): healthy animals with hydrophobic implants; H-HL (Healthy/Hydrophilic): healthy animals with hydrophilic implants; O-HB (Obese/Hydrophobic): animals with induced obesity and hydrophobic implants; O-HL (Obese/Hydrophilic): animals with induced obesity and hydrophilic implants. One hundred and twenty-eight implants were installed in the tibiae of the animals bilaterally (64 on the left tibiae and 64 on the right one) after 75 days of a specific diet (standard or high-fat diet) and euthanasia was performed in the experimental periods of 15 and 45 days after implant placement. Bone formation was assessed by biomechanical analysis (on the left tibiae of each animal), and microtomographic and histomorphometric analyses (on the right tibiae of each animal). Statistical analysis was performed using the Shapiro–Wilk test for normality and ANOVA followed by Tukey test to observe whether there was a significant difference between groups (p < 0.05); the t-test was used to compare the animals' body weight. Results: The biomechanical analysis showed an increase in the removal torque value of animals after 45 days in comparison to after 15 days, with the exception of O-HB groups. The microtomographic analysis demonstrated no significant differences in the mineralized bone tissue volume between the groups. In the histomorphometric analysis, the H-HL/45 day group/period demonstrated higher bone-implant contact, in comparison to H-HL/15 days and the O-HL/45 day group/period showed an increase in bone area between the implant threads, in comparison to O-HL/15 days. Conclusion: In conclusion, obesity does not interfere with the osseointegration of hydrophobic and hydrophilic implants.
Keywords: bone; dental implants; obesity; osseointegration; surface properties